Desain Kontrol Sistem Telemetri pH Larutan Nutrisi Hidroponik Berbasis Fuzzy Logic - Muhtar Muhtar; Zulmiftah Huda (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2019)
The utilization of bare areas like narrow tract, building roof, or unused warehouse can be maximized as agricultural land using hydroponics system. Hydroponics is a cultivation technique by using nutrient solution. The plant nutrient is an alternative soil which relate with water acidity (pH), that has reaction with nutrient solubility to plant fertility. In fact, pH of the nutrients can change because of many factors like media of plant. The temperature of nutrient solution affect an ion nutrient absorption by plant root. The higher temperature reduces plant root ability to absorb water and ion nutrients. The more advanced technological developments, the agriculture can be controlled automatically and monitored remotely. The aim of this research is to make design control ph, volume and nutrients solution using fuzzy logic and zigbee pro communication for telematics control of plant hydroponics. The result of this experiment shown that fuzzy logic has effectiveness to control pH of hydroponics. It needs 429 seconds to setting point of range pH 5 ppm to 7 ppm and 459 seconds to setting point of range pH 9 ppm to 7 ppm.